The Tortuous Ways of the Market: Looking at the European Integration of Higher Education from an Economic Perspective - Pedro Teixeira (London School of Economics and Political Science (LSE), European Institute, 2013)
European Higher education is facing times of significant change that has been affecting its identity and the political expectations regarding its societal roles. At the European level this has been fostered by a trend that increasingly regarded higher education as a tool for economic and social development. Hence, we have seen a reconfiguration of the sector alongside market rules, often through policy initiatives and government intervention. In this text we reflect about these developments by focusing in the emergence of a more integrated higher education area increasingly shaped by market forces and economic rationales. We reflect about the emerging and potential effects of greater integration in the European Higher Education Area.
Keywords: 330; EHEA; Markets; Integration; Inequality; Differentiation; Economics